The visual analogue scale in the assessment of grip strength. Issue 4 (August 1978) - Downie, W W; Leatham, P A; Rhind, V M; Pickup, M E; Wright, V
Abstract : The accuracy of information derived from a visual analogue scale has been assessed by comparing the measured grip strength of 100 subjects against their estimate of grip strength scored on a visual analogue scale. There was relatively poor correlation between the measured and assessed values, suggesting that similar inaccuracies may occur when the scales are used to assess subjective phenomena.